Gender-Based Violence Online in Tiktok Digital Culture: A Phenomenological Study on Women Tiktok Users in Indonesia - Tasya Ningrum Julia Anggraini; Syafrida Nurrachmi Febriyanti (International Journal of Social, Economic, and Business, 2025)
Gender-Based Violence Online (GBVO) is increasingly widespread with the increasing use of social media, especially TikTok which is the most popular digital public space among young women. While it offers a space for expression, TikTok also exposes the reproduction of misogyny, anti-feminism, and attacks on women's bodies in various forms. This study aims to understand the experiences of Indonesian women as victims of GBVO on TikTok and how they give meaning to the violence they experience in the emotional, social, and digital dimensions. This research uses a qualitative method with a digital phenomenology approach, referring to the thoughts of Simone de Beauvoir, Iris Marion Young, Sara Ahmed, and Silvano Tagliagambe. The data was obtained through in-depth interviews with five women who had experienced GBVO on TikTok. The results showed that women experienced multiple forms of GBVO such as sexually explicit comments, body shaming, gender-based hate speech, deepfakes, as well as threats and intimidation. This experience has an emotional impact in the form of fear, anger, shame, and anxiety that is inherent in the body and affects the way they interact in the digital space. Socially, women tend to withdraw themselves, change their way of expressing themselves, or self-censorship to avoid repeated violence. Although victims carry out various strategies such as blocking the perpetrator, reporting accounts, or deleting content, these actions have not been able to overcome patriarchal power structures that work through algorithms and digital culture. This study concludes that KGBO on TikTok is an existential experience that affects women's bodies, emotions, and identities while showing that digital space and real space merge in forming violent experiences. These findings underscore the need for collaborative efforts between users, platforms, and policymakers to create safer digital spaces for women.